Using of Memoization in Arithmetic Operations Sign Placement Problems (Моделювання, керування та інформаційні технології, 2019)
The article compares two ways of solving the arithmetic operations sign placement problem: method based on recursion and dynamic programming based one which uses the memoization. Limitations on the intermediate results of the problem solution are identified and justified. It is shown that the use of memoization to cut off ineffective search options makes it possible to accelerate the corresponding algorithms execution by tens times